The Effect of Earnings Per Share (EPS) and Debt To Equity Ratio (DER) On Stock Returns In The Consumer Goods Industry Sector on The Indonesia Stock Exchange - Zulkifli Setiok; Suriyanti; Arifin Sugianto; Zahrah Mukhtar; Sitti Zalsamalah; Rama Patawari (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2024)
The capital market serves as a platform for investors to allocate their capital, one of which is through stocks. This study aims to analyze the effect of Earnings Per Share (EPS) and Debt Equity Ratio (DER) on stock prices. The study utilizes secondary data, specifically the Annual Reports of Consumer Goods Industry Sector companies listed on the Indonesia Stock Exchange for the 2020–2023 period, obtained from the website www.idx.co.id. Respondent sampling was conducted using purposive sampling. The data analysis method employs a multiple linear regression analysis with a quantitative approach using a specialized application. The findings of this study reveal that: (1) Hypothesis testing results indicate that the earnings per share variable has a positive and significant effect on stock returns. (2) Hypothesis testing results also show that the debt equity ratio variable has a positive and significant effect on stock returns. This indicates that a higher debt-to-equity ratio impacts the increase in stock returns for consumer goods industry companies.